THE IMPACT OF TRANSFORMATIONAL CHANGES ON THE EFFECTIVENESS OF THE FUNCTIONING OF INNOVATION PARKS - KRYSOVATYY, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Innovation parks are key elements of modern innovation infrastructure aimed at the development of science, technology and support of entrepreneurship. In the conditions of rapid transformational changes caused by the development of digital technologies, globalization processes, growing requirements for environmental sustainability and social responsibility, innovative parks are faced with the need to adapt their business models and management approaches to maintain competitiveness and increase efficiency. The purpose of the presented work is to determine the features of the impact of transformational changes on the efficiency of the functioning of innovation parks. Methods used in the work: logical method, method of comparison, methods of analysis and synthesis, methods of deduction and induction, tabular and graphic methods for visual presentation of research results. It is also substantiated that the impact of transformational changes is manifested in the need for the integration of the latest technologies, digital solutions, as well as the application of innovative formats of cooperation, which leads to the rapid renewal of park infrastructure, the development of new services and approaches to knowledge management. Changes in the labor market, increased requirements for the qualifications of employees, and the intensification of work on projects focused on environmental sustainability make innovation parks centers of socio-economic progress and adaptation to the requirements of sustainable development. The impact of transformational changes is manifested in the need to integrate the latest technologies, digital solutions, as well as the use of innovative formats of cooperation, which leads to the rapid renewal of park infrastructure, the development of new services and approaches to knowledge management. Changes in the labor market, increased requirements for the qualifications of employees, and the intensification of work on projects focused on environmental sustainability make innovation parks centers of socio-economic progress and adaptation to the requirements of sustainable development. Thus, analyzing the impact of transformational changes on innovation parks is an important task for determining their role in the modern economy and finding effective solutions to preserve their relevance and effectiveness in the face of constant changes.